A Cultural and Spiritual Cityscape: Manila Chinatown in Charlson Ong’s Blue Angel, White Shadow - Lily Rose Tope (Asiatic: IIUM Journal of English Language and Literature, 2022)
Binondo, Manila’s Chinatown, is a sanctuary of the immigrant Chinese. It is a place where members of the Chinese community find things more familiar and comforting to them. As a commercial centre in Manila, its role in the economic life of Filipinos has often been highlighted. Charlson Ong’s novel, Blue Angel, White Shadows (2010), however, has painted it as the strange other, ominous and deadly. Ong’s contemporary Binondo is a place where identities have becomeintractable and Chineseness has become liminal. It has become an undesirable, frightening place where community disintegrates and humanity becomes a burden. The novel revolves around the mysterious death of a Filipino woman in Binondo. This article examines the existential and cultural questions that her death generates. Looking at Binondo as a dystopia, it will explore resulting ethnic anxieties and moral dilemma in the context of a Chinatown that has become more porous and therefore vulnerable to the unwanted socio-political osmosis from the external Filipino world.